FADS2 expression modulates effect of dietary polyunsaturated fatty acids on western diet-induced glucose intolerance - Linde, Peter, author; Chicco, Adam, advisor; Melby, Christopher, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2017)
Fatty Acid Desaturase 2 (FADS2) haplotypes associated with hyperactivity of its gene product, delta-6-desaturase (D6D), are associated with obesity and type-2 diabetes in humans. D6D regulates long-chain polyunsaturated fatty acid (PUFA) biosynthesis and is upregulated in several rodent models of obesity/insulin resistance, but its direct influence on diabetes is unclear. D6D activity might favor pathogenic effects of omega-6 FA linoleic acid (LA) by enhancing production of its product arachidonic acid (AA). Conversely, D6D may promote protective effects of omega-3 FA α-linolenic acid (ALA) by enhancing production of ALA to long-chain PUFAs that displace AA in cell membranes. It is hypothesized that abundant LA found in the modern western diet will be converted to AA promoting an inflammatory phenotype. The present study is to determine the interaction of heterozygous knockout (HET) or transgenic overexpression (TG) of FADS2 in mice fed high fat diets (HFD), as well as the interaction of LA:ALA content in the HFD. Adult male mice with HET (low), wild type (WT; medium), and TG (high) expression of FADS2 were fed HFD (45% w/w) containing 8% PUFA supplied by a balanced mix of LA and ALA (1:1), LA-rich (41:1), or ALA-rich (1:4) for 16 weeks. Glucose intolerance developed in WT mice, with no difference between diets. In HET mice, glucose intolerance was attenuated but this protection was removed by ALA rich diet. TG mice developed more glucose intolerance than WT. TG mice fed high LA diets were more glucose tolerant than high ALA and mixed diets. In conclusion, FADS2 expression modulates metabolic responses to high fat feeding. HET provides some protection against glucose intolerance, except when given an ALA rich diet. Transgenic overexpression increases glucose intolerance while a high LA diet attenuates this effect. This is inconsistent with current hypotheses that AA production from LA increases metabolic risk.
Keywords: inflammation; metabolism; lipids; diabetes